Molecular and phenotypic identification of Candida isolates from pregnant women in Ogbomoso, Southwestern Nigeria - Nurat, Akinbami Abidemi; Ola, Babalola Gbolahan; Olushola, Shittu Mujeeb; Mikhail, Tijani Aramide; Ayodeji, Adekola Saheed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Vulvovaginal candidiasis (VVC), often referred to as a yeast infection is a common gynaecologic disease, affecting 3 out of 4 women in their lifetimes. More than 40% of affected women will have 2 or more VVC episodes, and infection occurs more frequently in pregnant women. This study was carried out to provide information on the appropriate diagnostic method required to differentiate the causative agents of VVC among pregnant women. Methods: In this study, vaginal specimens were collected from one hundred (100) pregnant women aged between 17-44 years and of gestation age of 14-36 weeks who were attending antenatal clinic at LAUTECH Teaching Hospital, Ogbomoso. The species identification was performed using chromogenic medium, induction of fungal germ tube formation, and PCR using universal primers of internal transcriber spacer (ITS1 and ITS4); (ITS1 [5′-TCCGTAGGTGAACCTGCGG-3’] and ITS4 [5′-TCCTCCGCTTATTGATATGC-3’]) and Candida albicans-specific primers [5’-GGTTTGCTTGAAAGACGGTAG-3’] and [5’-AGTTTGAAGATATACGTGGTAG-3’] that target sequences site of the intergenic spacer region (ITS) of the fungal rRNA genes (18S and 28S) were used for this assay. Results: Forty (40) Candida species from 100 specimens were isolated in Saboraud dextrose agar (SDA) medium. Of 19 strains of C. albicans that were identified by chromogenic agar (CHROMagar), 17 were confirmed as true positive by PCR while 2 were false positive. The CHROMagar had 89.4% sensitivity and 90.4% specificity. In comparison, GTT was better in correctly identifying those strains that were confirmed as C. albicans by PCR (Sensitivity=94%) while CHROMagar was better in identifying the strains that were not confirmed as C. albicans by PCR (Specificity=90.4%). Conclusions: The combine uses of chromogenic agar and PCR have the advantage of efficient differentiation and identification of Candida species.